Microstructure and mechanical properties of silica hydrogels from sodium silicate solutions - Marzieh Matinfar; Anastasia Elias; John A. Nychka (Materials & Design)
Silica hydrogels from sodium silicate solutions show potential for composite bone scaffolds, but their mechanical properties are not fully understood. This study investigates how pH, waterglass concentration, and acid initiators affect the mechanical properties and microstructure of silica hydrogels. Real-time compression tests revealed three stress–strain behaviors: brittle fracture, plastic deformation with a plateau, and continuous strain hardening. Initial compressive strengths ranged from 7.3 to 9.9 MPa, increasing to 16–38 MPa (basic group) and 21–53 MPa (acidic group) after aging. Basic 1:3 (25 wt% waterglass) and acidic 1:1 (50 wt% waterglass) formulations exhibited the highest strengths in their group. Engineering stress overestimated true stress by 21–66 %. Correlating the gradient stress–strain curves with real-time observations of deformation stages under compression revealed the connection between critical transitions in the stress–strain curve and stages such as crack initiation, propagation, and fragmentation. Structurally, basic gels formed larger structural units and pores (3–5 µm), contributing to increased ductility, while acidic gels formed a denser network with smaller pores, contributing to brittle behavior. Dilution increased pore size to 15–20 µm in both groups. These findings provide valuable insights for optimizing the processing-structure–property relationship in silica hydrogels for composite bone scaffolds.